Pilot study: a descriptive-retrospective analysis of SARS-CoV-2 variants distribution and phylogenesis in the Phlegraean area - Mazzarella, Maria Cristina; Cristiano, Stefano; Rea, Dilia; Mazzarella, Nicola; Addeo, Martina; Iannelli, Silvia; Falco, Geppino; Brancaccio, Mariarita; Angrisano, Tiziana (Frontiers in Molecular Biosciences, 2025)
COVID-19 disease, caused by SARS-CoV-2 virus, marked the pandemic era, opening the way to next-generation sequencing in the viral diagnostic field. SARS-CoV-2 viral genome sequencing makes it possible to identify mutations in the virus and to track the diffusion of these variants in specific geographic area and in time. Variant sequences help understand how the virus spreads and how it can be contained, as well as for developing more effective vaccines and therapies. Indeed, monitoring the evolution of a virus allows us to quickly detect the potential selection of a super mutation, which can make a virus even more contagious and dangerous in terms of human health consequences. In light of this, in our pilot study, we decided to profile the SARS-CoV-2 genome, recruiting 38 patients divided according to age, sex, vaccination status and symptoms, ascertaining their positivity to the virus. Specific strains of SARS-CoV-2 have been identified and effective through next-generation sequencing. This analysis made it possible to obtain information on the variants of the virus and their spread in the Campania region of the Phlegraean area, in the municipalities of Bacoli, Pozzuoli and Monte di Procida from December 2021 to February 2023 and on the effect of long-term measures COVID-19 in our sample. The advantage of using NGS in diagnosis is the introduction of tests on many genes in a relatively short time and at relatively low costs, with a consequent increase in a precise molecular diagnosis and helps to identify ad personam therapies.